1903 Tenn. Pub. Acts 376-77, ch. 169, § 6. - (:unkn) unknown (My University, 1903)
[N]o person or persons shall . . . for the purpose of taking or destroying birds or animals not protected by this Act, use any swivel or punt gun, or gun other than a gun held in the hands and fired from the shoulder, and of the gauge not larger than No. 8[.]
Keywords: HUNTING REGULATION